The necessity of self-referential meta-rationality to neutralize the insight-behavior gap (or: How to render the insight-behavior gap ineffective) - Schnepf, Julia; Groeben, Norbert (Acta psychologica, 2025)
Most individuals view themselves as generally rational, yet empirical research in psychology reveals a persistent gap between rational insight and actual behavior. This paper introduces the concept of the insight-behavior gap, expanding on existing models like the intention-behavior and knowledge-behavior gaps. We focus particularly on climate-related behaviors, where rational understanding of necessary actions often fails to result in behavioral change. While self-regulation strategies offer some promise, they are insufficient at the societal level. We argue that bridging this gap requires self-referential meta-rationality: the recognition that insight alone is inadequate and must be supported by accepted external constraints. We propose that this form of rationality could enhance support for necessary regulatory measures such as carbon taxes. Psychology, we suggest, should play a key role in developing strategies to foster this deeper, self-critical form of rationality.